SPATIAL ANALYSIS OF HEALTH COMPLAINTS IN ACEH PROVINCE: SUSENAS SURVEY 2018 - Raisuli Ramadhan (Faculty of Public Health, Andalas University, 2020)
Health is a very basic need for everyone. However, health often becomes the downstream (impact) of various problems experienced by individuals and the surrounding environment. This study aims to map public health complaints per district / city to describe health problems in the community of Aceh Province in 2018.This research is a cross-sectional survey using Susenas data from Aceh Province in 2018. The population is all districts / cities in Aceh Province as many as 23 districts / cities taken with total sampling. The percentage parameter of health complaints is identified from the percentage factor of the population age> 65 years, the percentage of the population without a partner and the percentage of women. The spatial image was obtained using ArcMap 10.3 software. The results of the spatial mapping study showed that the percentage of public health complaints in Aceh Province in 2018 varied in each district / city. The percentage factor of age> 65 years and the percentage without a partner is not related to the percentage of health complaints, while the percentage of female population in several districts/cities is related and some is not related to public health complaints in Aceh Province in 2018.